FACTORS AFFECTING SOLVENCY IN INSURANCE COMPANIES IN INDONESIA 2015–2019 PERIOD - Rahayu Ningsih, Siti; Purwohedi, Unggul; Mardi (Transpublika Publisher, 2021)
Firm size, investment return ratios, self-retention ratios, and underwriting results are all being examined in this research to see how they affect solvency (proxied by the Risk Based Capital ratio). In this study, 74 insurance businesses registered with the Financial Services Authority (OJK) between 2015-2019 were studied. Using the purposive sampling method, a fair sample of 40 insurance companies was drawn over the course of five years. Consequently, the total number of observations was 200. Eviews 11, a program for panel data regression analysis, is used in this research. According to the findings of this study, insurance companies' solvency is affected by the Self-Retention Ratio and Underwriting Results. While the Firm Size and Investment Return Ratio have no effect on the solvency of insurance companies.